2023
DOI: 10.1128/spectrum.03445-22
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Humoral Responses to Two Doses of ChAdOx1 nCoV-19 Vaccination in Patients Receiving Maintenance Hemodialysis

Abstract: Patients with kidney failure have worse immune response following vaccination compared to general population, but few clinical studies have investigated immunogenicity of ChAdOx1 nCoV-19 (AZD1222) vaccination in hemodialysis patients. Here, we showed two doses of AZD1222 vaccines lead to high seroconversion rate of anti-SARS-CoV-2 receptor-binding domain (RBD) antibodies, and more than 80% patients acquired neutralizing antibodies against ancestral virus and delta variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
1
5
1
Order By: Relevance
“…At 6 months post 2nd dose, though seropositivity in HDs dropped further to 66.7%, MAB level of patients who remained seropositive had not changed significantly as those with low antibody levels had become seronegative while those with moderate to high antibody appeared able to maintain levels. This is in contrast to other studies where the decay of nAB levels following 2 doses has been shown consistently in both healthy individuals [ 52 , 53 ] and HD patients [ 50 , 54 – 56 ]. These studies varied in terms of the patient demographics (mean age, dialysis vintage, prior infection status etc.)…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At 6 months post 2nd dose, though seropositivity in HDs dropped further to 66.7%, MAB level of patients who remained seropositive had not changed significantly as those with low antibody levels had become seronegative while those with moderate to high antibody appeared able to maintain levels. This is in contrast to other studies where the decay of nAB levels following 2 doses has been shown consistently in both healthy individuals [ 52 , 53 ] and HD patients [ 50 , 54 – 56 ]. These studies varied in terms of the patient demographics (mean age, dialysis vintage, prior infection status etc.)…”
Section: Discussioncontrasting
confidence: 99%
“…HD patients were shown to maintain seropositivity at 98.3% four months after the third dose, though MAB levels reduced [ 16 ]. Importantly, low to moderate levels of Omicron neutralization were seen in patients only after either 3rd dose vaccination or post COVID-19 infection [ 50 , 57 ]. Further, while patients who had COVID-19 (after 2 previous doses) developed nAB levels similar to those who had 3rd dose vaccination (2200 -2500 IU/ml), those who had infection, had a 3.2 fold higher level of Omicron nAB compared to post vaccination individuals [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In December 2022, Beijing, China, witnessed a wave of SARS-CoV-2 infections dominated by the Omicron BF.7 variant. Weakened immune response, prolonged virus clearance, and low vaccination rate render patients undergoing hemodialysis particularly vulnerable [ 1–3 ]. A systematic review and meta-analysis investigating the mortality rate of coronavirus disease 2019 (COVID-19) among hemodialysis patients published in 2022 reported an infection rate of >10%, with a mortality rate of 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in continuous variables between groups were assessed with Mann-Whitney test or Wilcoxon signed-rank test. Even though the sVNT of 30% is arbitrarily set as the cut-off value for adequate neutralizing activity against SARS-CoV-2, a value <30% still represents neutralizing antibody level and correlates with anti-SARS-CoV-2 spike antibody even though it may not be enough to prevent most real life infection [ 28 ]. Therefore, we used the raw data of sVNT for further correlation analysis (Spearman correlation).…”
Section: Methodsmentioning
confidence: 99%